International taxing and trading carbon emissions: Distributional impacts of double regulation - Rüdiger Pethig; Thomas Eichner (Verein für Socialpolitik, 2010)
We focus on carbon emissions control in a group of countries to explore the distributional incidence of mixed policies consisting of a joint emissions trading scheme (ETS) and of national emissions taxes overlapping with the ETS. Such policies impact on national welfares through both the overlapping taxes and the distribution of national emissions caps. Our main result is that for every mixed policy, there exists an ETS policy without overlapping taxes yielding the same levels of national welfare as the mixed policy. We also suggest two measures of the net distributional incidence of mixed policies.
Keywords: H23; Q52; Q58; 330; emissions cap; emissions tax; emissions trading